Intimate Partner Violence and Intimate Partner Homicide: Development of a Typology Based on Psychosocial Characteristics - Vignola-Lévesque, Carolanne (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) remains an important and alarming global issue. Studies have put forth different profiles of perpetrators of IPV according to the severity of the violence and the presence of psychopathology. The objective of this study was to develop a typology of perpetrators of IPV and intimate partner homicide (IPH) according to their criminological, situational, and psychological characteristics, such as alexithymia. Alexithymia is when a person has difficulty identifying and describing emotions and in distinguishing feelings from bodily sensations of emotional arousal. Data were collected from 67 male perpetrators of IPV and/or homicide. Cluster analyses suggest four profiles: the homicial abandoned partner (19.4%), the generally angry/aggressive partner (23.9%), the controlling violent partner (34.3%), and the unstable dependent partner (22.4%). Comparative analyses show that the majority of the homicidal abandoned partners had committed IPH, had experienced the breakup of a relationship, and had a history of self-destructive behaviors; the generally angry/aggressive partners were perpetrators of IPV without homicide with a criminal history and who were alexithymic; the controlling violent partners had a criminal lifestyle and committed IPH; and the unstable dependent partners had committed IPV without homicide, were alexithymic, but had no criminal history. Establish a better understanding of the psychological issues within each profile of perpetrators of violence within the couple can help promote the prevention of IPV and can help devise interventions for these individuals.